CONSUMERS’ PERCEPTION of THE COST of CREDIT DEFAULT in THE VEHICLE FINANCE INDUSTRY in SOUTH AFRICA - Soga, Nomaphelo; Obokoh, Lawrence; Onojaefe, Darlington P.; Ukpere, Wilfred Isioma (Journal of Economic Development, Environment and People, 2021)
The risk that a borrower may not fulfill his/her borrowing obligation presents the credit owner (lender) a default risk management opportunity to maximize the risk-adjusted rate of return and to maintain minimum exposure to default associated cost. This paper investigated respondents’ perception of the cost of credit default and examines requirements for default risk management (DRM) in the vehicle finance industry in South Africa. It is noted that with an increased level of consumer indebtedness, unstable economy, high unemployment, opportunistic risks like health pandemics, vehicle financing faces a higher probability of default from borrowers. This descriptive investigation utilized a quantitative approach using a survey method to collect data from 381 purposive randomly selected respondents who are vehicle finance customers in South Africa, Cape Town specifically. Data collection took place in the Western Cape over a nine-month period, utilizing personal interviews, and emails to administer questionnaires to vehicle finances’ customers as data collection instruments. Responses received were codified and quantitative data were analysed using the Statistical Packages for Social Sciences (SPSS version 25) The paper found mixed and variable respondents’ perceptions of the cost of credit default. In conclusion, it is perceived that South Africa’s debt would become more costly with credit default. It can be recommended that a default risk management intervention be applied to manage credit default risk within the context of the unified credit assessment policy in South Africa.